Gendered opportunities and constraints to scaling up: a case study of spontaneous adaptation in a pastoralist community in Mwanga District, Tanzania. (19th May 2018) - Wangui, Elizabeth Edna; Smucker, Thomas Alan
Abstract : There is a growing momentum within development circles for pro-active strategies to facilitate the climate change adaptation of pastoralist communities. However, where planned adaptation originates outside a community, it has the potential to alter or eclipse autonomous forms of local adaptation. This paper identifies the range of autonomous adaptive practices undertaken by a Maasai pastoralist community and examines existing opportunities and constraints to adaptation. Field data were collected at three complementary levels: community, household and individual. Results indicate that many adaptive practices used in this community have been modified from past risk management strategies drawn directly from pastoralists' experience in dry-land environments. However, not all pastoralists are able to engage in these adaptive practices. Gender and wealth inequality pose a challenge to scaling up as they influence access to land and water for irrigation as well as financial assets required to access adaptive practices that are available in the wider community. This research concludes that planned adaptation should take into consideration the full range of existing adaptive practices and inequality in access as this provides information on opportunities and barriers to scaling up.